'You Just Have to Work with What You've Got' Practitioner Research with Precarious Migrant Families. Issue 2 (15th March 2018) - Jolly, Andy
Abstract : Undocumented migrant families experience high levels of food poverty, exclusion from mainstream benefits, and sometimes from social work services. This is an under-researched area for social work in the UK, and there is no statutory guidance for social workers on supporting undocumented migrants. Practitioner research is one way of 'visibilising' their experiences. Six migrant families accessing a voluntary sector stay and play project were interviewed using a practitioner research model of semi-structured interviews on the themes of food, access to services and children. The research found that families responded to their situation with a seemingly contradictory strategy of resignation and resilience. The implications for practitioners working with this user group are considered, and suggestions for support services for this group of families are offered.